A peptide encoded by a highly conserved gene belonging to the genus Streptomyces shows antimicrobial activity against plant pathogens - Jeon, Byeong Jun; Yoo, Nayeon; Kim, Jeong Do; Choi, Jaeyoung (Frontiers in Plant Science, 2023)
The genus Streptomyces has been unceasingly highlighted for the versatility and diversity of the antimicrobial agents they produce. Moreover, it is a heavily sequenced taxon in the phylum Actinobacteria. In this study, 47 sequence profiles were identified as proteins highly conserved within the genus Streptomyces. Significant hits to the 38 profiles were found in more than 2000 Streptomyces genomes, 11 of which were further conserved in more than 90% of Actinobacterial genomes analyzed. Only a few genes corresponding to these sequence profiles were functionally characterized, which play regulatory roles in the morphology and biosynthesis of antibiotics. Here a highly conserved sequence, namely, SHC-AMP (Streptomyces highly conserved antimicrobial peptide), which exhibited antimicrobial activity against bacterial and fungal plant pathogens, was reported. In particular, Arabidopsis thaliana was effectively protected against infection with Pseudomonas syringae pv. tomato DC3000 by treatment with this peptide. Results indicated the potential application of this peptide as an antimicrobial agent for control of plant diseases. Our results suggest putative target genes for controlling Streptomyces spp., including the one exhibiting antimicrobial activity against a wide range of phytopathogens.